ATRIBUTOS FÍSICOS DO SOLO EM DIFERENTES SISTEMAS DE MANEJO DO SOLO NO CERRADO - SOUZA, Danilo Filipe Andrade de; PANACHUKI, Elói; SANTOS, Wesley Vieira dos; MENEZES, Roniedison da Silva; NUNES, Lethicia Fernandes; FERREIRA, Ian Tales de Jesus (ANAIS DO ENIC, 2025)
-